2023
DOI: 10.1007/s00126-023-01222-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in antimony isotopic composition as a tracer of hydrothermal fluid evolution at the Sb deposits in Pezinok (Slovakia)

Andreas B. Kaufmann,
Marina Lazarov,
Stefan Weyer
et al.

Abstract: In this work, we investigated in situ isotopic compositions of antimony (Sb) minerals from two substages of the ore deposits near Pezinok (Slovakia). The δ123Sb values of the primary Sb minerals range from −0.4 and +0.8‰ and increase progressively along the precipitation sequence. In the substage II, the early-formed gudmundite (FeSbS) shows in all sections the lowest δ123Sb values, followed by berthierite (FeSb2S4), stibnite (Sb2S3), and valentinite (Sb2O3) with the heaviest δ123Sb values. A similar trend was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Spectrosc. 2024, 45 (1), 33-43. methylation in biological processes, 8 adsorption processes, [9][10][11][12][13][14] evaporation and precipitation processes, 10,15 mixing processes, 16 and Rayleigh fractionation processes. 17 This characteristic makes Sb isotope composition a valuable tracer in the field of ore deposits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectrosc. 2024, 45 (1), 33-43. methylation in biological processes, 8 adsorption processes, [9][10][11][12][13][14] evaporation and precipitation processes, 10,15 mixing processes, 16 and Rayleigh fractionation processes. 17 This characteristic makes Sb isotope composition a valuable tracer in the field of ore deposits.…”
Section: Introductionmentioning
confidence: 99%
“…17 This characteristic makes Sb isotope composition a valuable tracer in the field of ore deposits. 7,15,17,18 Recent research has revealed significant variations in Sb isotope ratios in Sb-bearing mineral deposits, with a maximum δ 123 Sb range exceeding 1‰. 6,7,15,17,19,20 As the geological database and fractionation theories of Sb isotopes continue to advance, the application prospects of Sb isotopes are poised to be extensive, offering valuable insights into redox changes in hydrothermal ore-forming systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,27,46 Enhancing comprehension of the process of fractionation during adsorption can provide valuable insights into the utilization of isotope tracer approaches. 24,27,47 Iron (oxyhydr)oxides are common minerals in soils and sediments and exert significant effects on the (bio)geochemistry of metal pollutants. 48 Several studies have investigated the adsorption behavior of Sb absorbed on ferrihydrite, goethite, and hematite.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research on nontraditional stable isotopes indicates adsorption is commonly recognized as a significant mechanism that often leads to stable isotope fractionation. , The adsorption of Zn onto iron (oxyhydr)­oxides results in the enrichment of heavy isotopes yet iron (oxyhydr)­oxides prefer to absorb light Ni isotopes. , The fractionation magnitude can also vary for different iron (oxyhydr)­oxides. The migration of Sb can be affected by the presence of Fe (oxyhydr)­oxides in both soil and aqueous environments . The affinity of Sb­(V) toward the iron oxides depends on Sb species, pH, and the characteristics of iron (oxyhydr)­oxides, and the bidentate mononuclear edge-sharing complex is involved in the adsorption process. , The process of heavy isotope enrichment in mine drainage water can be attributed to the adsorption of Sb­(OH) 6 – on Fe hydroxides. ,, Enhancing comprehension of the process of fractionation during adsorption can provide valuable insights into the utilization of isotope tracer approaches. ,, …”
Section: Introductionmentioning
confidence: 99%